Structural and local physical properties of relaxor ferroelectric thin films - Melo, Michael de [UNESP] (2017)
Polycrystalline thin films of Pb0.91La0.09Zr0.65Ti0.35O3 (PLZT9/65/35) and Sr0.75Ba0.25Nb2O6 (SBN75) were prepared by the chemical polymeric routine in order to investigate their physical properties at the macro- and nanoscale. X-ray diffraction (XRD), piezoresponse force microscopy (PFM), and scanning electron microscopy (SEM) were used as investigative tools. PLZT9/65/35 and SBN75 thin films have exhibited perovskite and tungsten bronze crystal structure at room temperature, as it was expected in this nominal composition for these relaxor ferroelectric materials. In addition, Rietveld method of the crystalline structure has revealed the thickness dependence of the crystallite size, grain size, and microstrain. The transition temperature of SBN thin film showed to shift to lower temperatures, suggesting the presence of a higher defect concentration, such as oxygen vacancies, chemical disorder, and lattice defects in this film. SEM has exhibited the porosity features in both thin films and has confirmed the existence of chemical elements (such as oxygen, niobium, lanthanum, strontium, platinum, silicon and barium) in film surface and near the substrate. Ferroelectric properties have been investigated by PFM and the results have suggested a thickness and crystallite size dependence of the piezoelectric response. Also in this work, the dynamic of ferroelectric domain switching and the induced domain relaxation were studied using the switching spectroscopy PFM (SS-PFM) in both relaxor systems as a function of variable DC applied voltages and pulse durations.